2001
DOI: 10.1348/096317901167497
|View full text |Cite
|
Sign up to set email alerts
|

Well‐being and occupational health in the 21st century workplace

Abstract: Over the last 40 years, major changes have taken place in the workplace. The growth in the use of information technology at work, the globalization of many industries, organizational restructuring, changes in work contracts and worktime scheduling have radically transformed the nature of work in many organizations. The workforce itself is also diversifying, with an increase in female participation, a growing number of dual‐earner couples and older workers. The present paper discusses the impact of these workpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
337
0
27

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 483 publications
(387 citation statements)
references
References 77 publications
6
337
0
27
Order By: Relevance
“…Work is not merely a source of livelihood; for many, work fulfills intrinsic needs such as motivation, belonging, and accomplishment (Warr & Wall, 1975). The second is the impact of worker well-being on his or her performance, which can subsequently shape service provision and client outcomes (Burton, 2010;Danna & Griffin, 1999;Ford, Cerasoli, Higgins, & Decesare, 2011;Sparks, Faragher, & Cooper, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Work is not merely a source of livelihood; for many, work fulfills intrinsic needs such as motivation, belonging, and accomplishment (Warr & Wall, 1975). The second is the impact of worker well-being on his or her performance, which can subsequently shape service provision and client outcomes (Burton, 2010;Danna & Griffin, 1999;Ford, Cerasoli, Higgins, & Decesare, 2011;Sparks, Faragher, & Cooper, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Control variables: Earlier studies have shown that demographic variables, such as age (Cunningham et al, 2008), gender (Torkelson & Muhonen, 2008), occupational position (Sparks, Faragher & Cooper, 2001) and job tenure (Bernhard-Oettel, Sverke & De Witte, 2005) can be related to employee health and well-being. There are indications that these demographic variables are related to employee well-being in China too (Siu, Spector, Cooper & Lu, 2005), even though cultural differences such as Chinese (Confucian) work values (Ip, 2009) might produce different patterns of relations than in the west (Lok & Crawford, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…model of job insecurity discussed both the objective situation and subjective characteristics of one's job (e.g., perceived threats to one's job) as predictors of perceived job insecurity. Sparks, Faragher, and Cooper (2001) argued that the available research suggests that perceived job insecurity has negative effects on employee well-being, which can then negatively impact organizations. Within the cannabis industry, the objective security and stability of one's job might be obscure, given possible changes in the political climate regarding legalization of cannabis sale and use.…”
Section: Stigmamentioning
confidence: 99%